Cancer Risk and Multiple Sclerosis: Evidence From a Large Italian Cohort - D'Amico, Emanuele; Chisari, Clara G.; Arena, Sebastiano; Zanghì, Aurora; Toscano, Simona; Lo Fermo, Salvatore; Maimone, Davide; Castaing, Marine; Sciacca, Salvatore; Zappia, Mario; Patti, Francesco (Frontiers in Neurology, 2019)
Introduction: The complexity of understanding cancer risk in MS is increased by inconsistencies in study design, and the lack of age-, sex-, and ethnicity-specific risk estimates. Aims of our study were to estimate the incidence of cancers in the MS population of Catania (Italy) and to evaluate the impact of disease-modifying treatments (DMTs) in cancer risk. Materials and Methods: We screened 2,730 PwMS according to the MS criteria of Mc Donald 2010 referring to MS center of Catania in the period between 2003 and 2013. We matched database of MS patients with the Integrated Cancer of Catania-Messina-Siracusae-Enna. We calculated age and sex specific standardized incidence ratios (SIR) and the relative risk (RR) of developing cancer in MS patients treated with at least two different DMTs compared to who received one or no treatment. Results: Out of 2,730, 1,180 MS patients (67.1% females; mean age 41.2 ± 12.9) were enrolled. We found 36 cancers. Global SIR was 1.18 (CI95% 0.78–1.58), with a significantly higher risk in men with a range age of 20 to 50 years [2.84; (CI95% 1.59–4.09)] and in women over 50 years [1.82 (CI95% 1.08–2.55)]. RR of developing cancer was 1.99 (CI95% 1.14–3.45) in MS patients switching one DMT and 3.38 (CI95% 1.83–6.22) in who switched at least twice. Discussion: Our results demonstrated that cancer risk was not increased in our MS population; but age and sex different distribution may partly drive cancer risk. Higher cancer risk in MS patients switching more than two DMTs should take into account in treatment decision making.